2000
DOI: 10.1007/s004230000177
|View full text |Cite
|
Sign up to set email alerts
|

How to proceed in patients with carcinoma detected after laparoscopic cholecystectomy

Abstract: Carcinoma of the gallbladder is a rare disease. Gallbladder carcinoma is detected in less than 1% of all gallstone operations. With the introduction of laparoscopic surgery and the higher acceptance of this technique, gallbladders are now removed much earlier than they used to be. With the increase of cholecystectomies, the diagnosis of unexpected gallbladder carcinoma became more frequent. We report on how to proceed in patients with a diagnosis of gallbladder carcinoma and discuss the additional problems tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…For pT2 or more advanced tumors, many authors advocate radical resection with lymph node dissection [10][11][12][13][14] . Previous reports have shown a second radical resection to be associated with significantly better survival than cholecystectomy alone in pT2 GBCa patients whose cancers were incidentally found after cholecystectomy [15][16][17][18] , whereas, Wakai et al [19] have reported that 40.5% of patients with unapparent pT2 tumors survived > 5 years after cholecystectomy alone. S4a5 hepatectomy combined with extra-hepatic bile duct resection (BDR) and D2 lymph node dissection is a highly recommended operation for the treatment of T2 and T3 GBCa [6] , although, in T2 GBCa, the surgical procedure remains controversial, and there is no standard operation.…”
Section: Introductionmentioning
confidence: 96%
“…For pT2 or more advanced tumors, many authors advocate radical resection with lymph node dissection [10][11][12][13][14] . Previous reports have shown a second radical resection to be associated with significantly better survival than cholecystectomy alone in pT2 GBCa patients whose cancers were incidentally found after cholecystectomy [15][16][17][18] , whereas, Wakai et al [19] have reported that 40.5% of patients with unapparent pT2 tumors survived > 5 years after cholecystectomy alone. S4a5 hepatectomy combined with extra-hepatic bile duct resection (BDR) and D2 lymph node dissection is a highly recommended operation for the treatment of T2 and T3 GBCa [6] , although, in T2 GBCa, the surgical procedure remains controversial, and there is no standard operation.…”
Section: Introductionmentioning
confidence: 96%
“…It is well known for its poor prognosis, and 15-30% of patients show no preoperative or intraoperative evidence of gallbladder cancer (2). Gallstone disease, porcelain gallbladder, sclerosing cholangitis, and advanced age are the best known risk factors for gallbladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Most surgeons recommend no additional treatment for patients with early-stage disease. Five-year survival rates vary from 80% to 100% [4,15]. Shirai [16] has suggested that a second radical operation may not be beneficial to early incidental gallbladder cancer if the surgical margins are tumor-free.…”
Section: Discussionmentioning
confidence: 97%